OPTIMASI EKSTRAKSI DAUN NANGKA KUNING (Vincetoxicum villosum (Blume) Kuntze) DARI BERBAGAI PELARUT DAN METODE - Oktoviani, Oktoviani; Taurina, Hilda; Triana, Dessy; Rahmawati, Suci; Sari, Yulita Gumala; Melati, Putjha; Sari, Delia Komala (Universitas Bengkulu, 2022)
Extraction of a plant in traditional medicine is a very crucial stage for the success of the treatment. For example, nangka kuning (Vincetoxicum villosum (Blume) Kuntze) which has been scientifically researched, its leaves are extracted with ethanol solvent using the maceration method. Meanwhile, by local people,nangka kuning leaves are processed by boiling using water. This attracted the attention of researchers to re-analyze the content of secondary metabolites in nangka kuning leaf extract made with different solvents and methods. Researchers carried out the extraction using water with heating (infusion), ethanol without heating (maceration) and chloroform without heating (maceration). The results obtained from the three types of extracts contained secondary metabolites of alkaloids in the three extracts. While steroids are only found in extracts with a water solvent. Then the tannins are found in the extract with water and ethanol as solvents. Negative results from the three extracts were shown for secondary metabolites of flavonoids and saponins. So it can be concluded that nangka kuning leaf extract which has the most optimal secondary metabolite is the extract using water as a solvent by heating.